Investigating the bio-rejuvenator effects on aged asphalt through exploring molecular evolution and chemical transformation of asphalt components during oxidative aging and regeneration. (20th December 2021) - Hu, Dongliang; Gu, Xingyu; Dong, Qiao; Lyu, Lei; Cui, Bingyan; Pei, Jianzhong
Abstract: Using a rejuvenator to increase the dose of reclaimed asphalt pavement (RAP) materials in asphalt mixtures is a sustainable practice in the pavement industry. However, the mechanism by which the rejuvenator restores the performance of aged asphalt in the RAP binder remains an open question: research approaches are inadequate, and the details of asphalt aging are not clear. Here, we first revealed the aging mechanism of asphalt and obtained realistic structures of aged asphalt molecules by means of first-principles molecular simulations that modeled the chemical reaction between asphalt and oxygen. Subsequently, through classical modeling approaches that examine the solubility behaviors of asphalt molecules in n-heptane with and without a rejuvenator, we demonstrated the serious agglomeration of aged molecules, the transformation of aged resins into asphaltenes, and the restorative effect of the rejuvenator. To explore the driving force behind these findings, we performed density functional theory calculations and wavefunction analyses to determine the strength and nature of intermolecular interactions between asphalt molecules. The results indicated that the electrostatic interaction between aged asphalt molecules increases significantly upon generation of polar groups, and the rejuvenator decreases the electrostatic interaction mainly by eliminating hydrogen bonds, thus reducing molecular agglomeration, but has little effect on the dispersion force. Besides, Hansen solubility parameters were calculated to illustrate the agglomeration in aged asphalt and the restorative effect of the rejuvenator in terms of the "like-dissolves-like" rule. This study bridges the gap between electronic-scale modeling and complex engineering practice related to the aging and rejuvenation of asphalt. Graphical abstract: Image 1